Let's simplify the expression step by step:
The given expression is: \[ 5.5 + 7 \left[ (6.3 + 2.1) \times 4 + (10 - 4) \div 2 \right] \]
-
Calculate the expressions in the parentheses:
-
For \(6.3 + 2.1\): \[ 6.3 + 2.1 = 8.4 \]
-
For \(10 - 4\): \[ 10 - 4 = 6 \]
-
-
Now substitute back into the expression: \[ 5.5 + 7 \left[ (8.4) \times 4 + (6) \div 2 \right] \]
-
Calculate \( (8.4) \times 4 \): \[ 8.4 \times 4 = 33.6 \]
-
Calculate \( 6 \div 2 \): \[ 6 \div 2 = 3 \]
-
Combine the results in the brackets: \[ 33.6 + 3 = 36.6 \]
-
Now, substitute that back into the expression: \[ 5.5 + 7 \left[ 36.6 \right] \]
-
Calculate \( 7 \times 36.6 \): \[ 7 \times 36.6 = 256.2 \]
-
Finally, add \( 5.5 \) to that result: \[ 5.5 + 256.2 = 261.7 \]
Thus, the simplified expression equals: \[ \boxed{261.7} \]
The correct answer is D. 261.7.